Excess hospitalization expenses attributable to type 2 diabetes mellitus in Singapore - Png, M; Yoong, J; Tan, C; Chia, K (Elsevier, 2018)
Objective: To estimate the excess hospitalization expenses attributable to type 2 diabetes mellitus (T2DM) in a high-income Asian country from the health system perspective and the patient perspective. Methods: Electronic medical records from a tertiary academic hospital in Singapore from 2012 to 2013 were used to create propensity score–matched cohorts with and without T2DM on the basis of their entry characteristics. A two-part model was then used to control for remaining differences between the cohorts. Excess cost due to diabetes was defined as the difference in hospital expenses between a patient with diabetes and a matched patient without diabetes. As part of the sensitivity analysis, a two-part model without matching and different matching algorithms were used to obtain the range of hospitalization expenses attributable to patients with T2DM. Balance of covariates after matching was investigated. All costs were presented in 2013 US dollars. Results: Mean adjusted excess hospital expense of one hospital visit attributable to diabetes was approximately $1007 and $113 from the health system perspective and the patient perspective, respectively. For the cohort of patients with T2DM in Singapore, this amounts to a total average expenditure of $117 million and $13 million from the health system perspective and the patient perspective, respectively. Conclusions: Hospitalization expenses from diabetes result in a significant cost to the health care system in Singapore. Nevertheless, the excess burden of hospitalization on patients is mitigated significantly by cost sharing, which may reduce financial incentives to avert admissions through preventative care, which is largely out-of-pocket.